Preparation method of solid electrolyte, lanthanum titanium oxide compound and preparation method thereof
Through the sintering method of lanthanum titanium oxide compound and lithium source, a high-purity and high crystallinity lithium lanthanum titanium oxide compound solid electrolyte was prepared, which solved the problems of low conductivity and difficulty in batch production in the prior art, and achieved efficient Solid electrolyte production.
Patent Information
- Application Number
- CN202210379025.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-04-12
AI Technical Summary
The current inorganic solid electrolyte has low conductivity and cannot meet commercial requirements. It is difficult to achieve mass production during solid phase synthesis.
By mixing the lanthanum titanium oxide compound with a lithium source and sintering it, a lithium lanthanum titanium oxide solid electrolyte with a perovskite structure is prepared, which shortens the time for the lithium source to participate in the reaction and reduces the loss and waste of lithium raw materials.
The purity and crystallinity of lithium lanthanum titanium oxide compound are improved, its electrochemical properties are enhanced, and the mass production of solid electrolytes and high conductivity are achieved.
Smart Images

Figure CN114678587B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of green energy, and specifically to a method for preparing a solid electrolyte, a lanthanum titanium oxide compound and a lithium battery. Background Art
[0002] At present, facing the requirements of sustainable development of energy and ecological environment, it is of great significance to develop energy storage systems with higher energy density and environmental friendliness. Lithium-ion batteries (LB) have dominated energy storage devices since their commercialization. Lithium-ion batteries have been widely used in most electronic products, including electric vehicles as large energy storage devices. Most of the widely used lithium-ion batteries use liquid electrolytes, which have hidden safety risks and have endangered the application of lithium batteries. Compared with liquid electrolytes, the outstanding advantage of inorganic solid electrolytes is its non-flammability, which can make up for the shortcomings of liquid electrolytes. In addition, its higher mechanical strength can effectively inhibit the piercing of lithium dendrites during battery cycling, making the application of lithium metal possible. This allows researchers to focus more on the research of inorganic solid electrolytes.
[0003] The biggest obstacle to the practical application of most inorganic solid electrolytes is that their conductivity is very low, far from the conductivity required for commercial use. -3 S / cm. In the case of perovskite-type ABO3 (A = La, Sr or Ca; B = Al or Ti) inorganic solid electrolyte, Li can be introduced into the perovskite at the A position to form a lithium lanthanum titanium oxide solid electrolyte. The total conductivity of the lithium lanthanum titanium oxide solid electrolyte is mainly controlled by the grain boundary conductivity, and its room temperature ionic conductivity is as high as 10 -3 S / cm or above, close to the level of commercial electrolytes. Lithium lanthanum titanium oxide solid electrolytes also have the advantages of stable structure, simple preparation process, and a wide range of variable components.
[0004] The study found that different synthesis methods of lithium lanthanum titanium oxide compounds also have a certain influence on the structure of the electrolyte. Therefore, it is very important to synthesize stable single-phase lithium lanthanum titanium oxide compounds, which determines whether lithium lanthanum titanium oxide solid electrolytes can be widely promoted and applied. Common methods for synthesizing lithium lanthanum titanium oxide compounds mainly include sol-gel method, liquid phase precipitation method and solid phase method. Among them, expensive alcohol salts are used in the synthesis process of sol-gel method, resulting in high preparation cost. This method is only suitable for laboratory research; another liquid phase precipitation method also has some defects in the synthesis process. For example, it is difficult to use technical means to control the dissolution process of titanium salts, and it is also not suitable for industrial production; in comparison, the solid phase method has become the preferred process for mass production due to its simple equipment requirements and low raw material costs.
[0005] However, the current process for synthesizing lithium lanthanum titanium oxide by solid-phase method in the market is difficult to achieve mass production, and the main reasons are as follows: 1) The reaction time of the lithium source is too long. The long-term high-temperature calcination will lead to high energy consumption and cause the volatilization and loss of lithium salts, resulting in the instability of the single phase of the product lithium lanthanum titanium oxide, the formation of impurity phases, and finally the low purity and accuracy of the product, which cannot meet the application requirements of lithium lanthanum titanium oxide solid electrolyte in lithium-ion batteries; 2) Due to the large loss of lithium source during the reaction process, in actual production, the lithium source is often added according to the experience of technicians, resulting in the inability to mass-produce lithium lanthanum titanium oxide with a stable single phase. Summary of the Invention
[0006] The present application provides a preparation method of a solid electrolyte, a lanthanum titanium oxide and a preparation method thereof, which improve the purity and crystallinity of the product, reduce the loss and waste of lithium raw materials at the same time, and realize the mass production of the solid electrolyte.
[0007] The first aspect of the present application is to provide a lanthanum titanium oxide, which includes:
[0008] Mix the lanthanum titanium oxide with a lithium source to obtain a mixed material;
[0009] Sinter the mixed material to obtain lithium lanthanum titanium oxide with a perovskite structure, that is, the solid electrolyte;
[0010] Among them, the chemical formula of the lanthanum titanium oxide is La 2 / 3-x TiO3, where 0 < x < 0.16.
[0011] Optionally, in some embodiments of the present application, the total molar ratio of the lanthanum titanium oxide to the lithium lanthanum titanium oxide is (5 - 3x):(6x + 5), where 0 < x < 0.16; and the addition amount of the lithium source is 1.05 to 1.10 times the molar amount of lithium in the lithium lanthanum titanium oxide.
[0012] Optionally, in some embodiments of the present application, the sintering temperature is 900°C - 1000°C; and / or, the sintering time is 8h - 20h.
[0013] Optionally, in some embodiments of the present application, the particle size of the lanthanum titanium oxide is 5μm - 15μm; and / or,
[0014] The particle size of the lithium source is 5μm - 15μm.
[0015] The second aspect of the present application is to provide a lanthanum titanium oxide, and its chemical formula is: La 2 / 3-x TiO3, where 0 < x < 0.16.
[0016] Optionally, in some embodiments of the present application, the X-ray diffraction pattern of the lanthanum titanium oxide compound contains characteristic diffraction peaks at 2θ angles of 32±1 degrees, 40±1 degrees and 46±1 degrees.
[0017] The third aspect of the present application is to provide a method for preparing a lanthanum titanium oxide compound, which comprises:
[0018] mixing a lanthanum source compound having a particle size of micrometer size with a titanium source compound having a particle size of micrometer size to obtain a mixture;
[0019] Wet-grinding the mixture to obtain a slurry containing mixed particles with nanometer particle sizes;
[0020] Drying the slurry to obtain dry powder;
[0021] The dry powder is sintered to obtain lanthanum titanium oxide compound.
[0022] Optionally, in some embodiments of the present application, the molar ratio of the lanthanum source compound to the titanium source compound is (1-5):(2-4).
[0023] Optionally, in some embodiments of the present application, the sintering temperature is 900°C-1200°C; and / or the sintering time is 10h-48h; and / or during the mixing, a sintering aid is added to the raw materials; and / or the sintering aid is an oxide.
[0024] Optionally, in some embodiments of the present application, the mixing is wet mixing, and the mass percentage concentration of solids in the mixture is 12%-13%; and / or the drying is atomization drying.
[0025] Correspondingly, the fourth aspect of the present application is to provide a lithium battery, which includes the solid electrolyte prepared by the above preparation method; or includes the above lanthanum titanium oxide compound; or includes the lanthanum titanium oxide compound prepared by the above preparation method.
[0026] The process of the present application is simple, and the prefabricated lanthanum titanium oxide compound is sintered with a lithium source to form a lithium lanthanum titanium oxide compound. Compared with the traditional synthesis method, the time for the lithium source to participate in the reaction is greatly shortened, and the loss and waste of lithium raw materials caused by long-term high-temperature sintering is avoided, thereby reducing the cost and loss of lithium raw materials in the process of synthesizing perovskite-type solid electrolytes; at the same time, the formation of impurity phases can be effectively prevented, and the problem that the existing solid-phase method for preparing perovskite-type solid electrolytes cannot stably form lithium lanthanum titanium oxide compounds with a single phase due to the inability to quantitatively add lithium sources, resulting in the inability to achieve mass production of perovskite-type solid electrolytes.
[0027] The lithium lanthanum titanium oxide compound prepared in the present application has good phase homogeneity and no impurity phase is generated, which improves the crystallinity and purity of the product, thereby improving the electrochemical properties of the lithium lanthanum titanium oxide compound and further improving the conductivity of the lithium lanthanum titanium oxide solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 is an X-ray powder diffraction pattern (XRD) of the lanthanum titanium oxide compound prepared in the present application;
[0030] Figure 2 is an X-ray powder diffraction (XRD) pattern of the lithium lanthanum titanium oxide compound prepared in the present application;
[0031] Figure 3 It is XRD standard card JCPDS NO.87-0935. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application and are not used to limit the present application. In the present application, unless otherwise stated, the directional words used, such as "up", "down", "left", and "right", generally refer to the up, down, left, and right of the device in actual use or working state, specifically the drawing direction in the accompanying drawings.
[0033] The present application provides a method for preparing a solid electrolyte, a lanthanum titanium oxide compound and a method for preparing the same, and a lithium battery, which are described in detail below. It should be noted that the description order of the following embodiments is not intended to limit the preferred order of the embodiments of the present application. In the following embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, please refer to the relevant description of other embodiments.
[0034] An embodiment of the present application provides a method for preparing a solid electrolyte, which comprises:
[0035] Mix the lanthanum titanium oxide with a lithium source to obtain a mixed material; sinter the mixed material to obtain a lithium lanthanum titanium oxide with a perovskite structure, i.e., a solid electrolyte; wherein, the chemical formula of the lanthanum titanium oxide is La 2 / 3-x TiO3, where 0 < x < 0.16, and the value of x can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, etc. Of course, the value of x can also be any other value within the range of 0 - 0.16. The chemical formula of the lithium lanthanum titanium oxide is: Li 3x La 2 / 3-x TiO3. In other embodiments, the highest lithium ion conductivity in the perovskite-type solid electrolyte prepared by the above method is Li 0.33 La 0.56 TiO3, and the conductivity is 10 -3 S / cm. Because from the cubic perovskite structure of Li 3x La 2 / 3- x TiO3, it can be seen that the Ti atoms coordinated with oxygen atoms octahedrally occupy the cube corners, and the cube center is occupied or vacant by La 3+ 、Li ions, and its ionic conductivity is directly affected by the concentration of vacancies and the interaction force between lithium ions and the coordination framework. The highest lithium ion conductivity in the perovskite-type solid electrolyte is Li 0.33 La 0.56 TiO3. Of course, by using the above method, it is also possible to prepare Li 0.55 La 0.35 TiO3 with compatible stability for different cathode materials.
[0036] In the above preparation method, in the preparation method of the solid electrolyte, a special lanthanum titanium oxide is used as the raw material. The lanthanum titanium oxide is a new material prepared by a preparation method of lanthanum titanium oxide provided by this application. The specific preparation method is described in detail below. The lithium source can be selected from any one of lithium salts such as LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, Li CO, etc. All of the above lithium salts can be obtained by purchasing from the market.
[0037] In some embodiments, after obtaining the solid electrolyte, the particle size of the lithium lanthanum titanium oxide can be controlled within the required range by sanding or other grinding methods according to customer requirements.
[0038] In some embodiments, the total molar ratio of the lanthanum titanium oxide to the lithium lanthanum titanium oxide is (5 - 3x):(6x + 5), where 0 < x < 0.16; that is, the lanthanum titanium oxide is based on the lithium lanthanum titanium oxide Li3x La 2 / 3-x The molar ratio of lithium, lanthanum and titanium in TiO3 is 3x: (2 / 3-x): 1. The amount of lithium source added is 1.05 to 1.10 times the molar amount of lithium in the lithium lanthanum titanium oxide compound. 3x La 2 / 3-x The molar ratio of TiO3 is 5%-10% in excess of the lithium source. Because the preparation method of the present application sinters the prefabricated lanthanum titanium oxide compound with the lithium source to form a lithium lanthanum titanium oxide compound, which shortens the time for the lithium source to participate in the reaction, the present application can achieve accurate and controllable addition of the lithium source, that is, a small amount of excess addition, rather than a large amount of excess addition based on experience, which is conducive to the formation of a stable single-phase product, while avoiding the waste of the lithium source and reducing the cost of adding the lithium source. Experiments have shown that although the amount of lithium source added by the present application is less than that of the lithium source added in the prior art, the yield does not decrease significantly. In other embodiments, the particle size of the lanthanum titanium oxide compound is 5μm-15μm; the particle size of the lithium source is 5μm-15μm. The particle size of the lanthanum titanium oxide compound and the lithium source adopts the above-mentioned size parameters, which is conducive to increasing the reaction activity of the product, thereby facilitating improving the crystallinity of the final product. For example, in a specific example, the average particle size of the lanthanum titanium oxide compound can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, or any other particle size within the range of 5 μm-15 μm. The average particle size of the lithium source can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, or any other particle size within the range of 5 μm-15 μm.
[0039] In other embodiments of the present application, the lanthanum titanium oxide compound is mixed with a lithium source and then sintered, wherein the sintering may adopt the following process parameters: sintering temperature 900°C-1000°C; and / or, sintering time 8h-20h. Because the sintering temperature of the existing related process is 900°C-1200°C, and the sintering time is 10h-30h. The solid phase method of the present application has a low sintering temperature and a short sintering time. In a specific example, the sintering temperature may be any temperature of 900°C, 920°C, 950°C, 980°C or 1000°C, or any other temperature in the range of 900°C-1000°C; the sintering time may be 8h, 9h, 12h, 14h, 16h, 18h or 20h; or any other temperature in the range of 8h-20h. Controlling the sintering process parameters within the above range is conducive to the formation of grain gaps during the reaction, which helps to improve the conductivity of the solid electrolyte; at the same time, it is conducive to the formation of a single-phase product, thereby helping to improve the crystallinity of the product.
[0040] In some other embodiments of the present application, a lanthanum titanium oxide compound is provided, and its chemical formula is: La 2 / 3-x TiO3, where 0 < x < 0.16. In the X-ray powder diffraction pattern, 3 main characteristic diffraction peaks and 4 minor peaks appear at the diffraction angle 2θ in the range of 20° - 80°. The 2θ angles of the 3 main characteristic diffraction peaks are respectively at 32 ± 1 degree, 40 ± 1 degree, and 46 ± 1 degree, and the 5 minor peaks are respectively at 27 ± 1 degree, 30 ± 1 degree, 58 ± 1 degree, 68 ± 1 degree, and 77 ± 1 degree. In other embodiments, the lanthanum element, titanium element, and oxygen element are mixed according to the following mass percentages: the lanthanum element is 30% - 50%, the titanium element is 10% - 30%, and the oxygen element is 10% - 35%. After mixing, the lanthanum titanium oxide compound is obtained by sintering.
[0041] In some other embodiments of the present application, a preparation method of a lanthanum titanium oxide compound is provided, which includes:
[0042] Mixing a lanthanum source compound with a micron-sized particle diameter and a titanium source compound with a micron-sized particle diameter to obtain a mixture;
[0043] Performing wet grinding on the mixture to obtain a slurry containing mixed particles with a nano-sized particle diameter;
[0044] Drying the slurry to obtain a dry powder;
[0045] Sintering the dry powder to obtain a lanthanum titanium oxide compound.
[0046] Because the nano-sized particle diameter is small, particle agglomeration easily occurs during the grinding process during mixing, which will lead to non-uniform heat conduction, thus easily generating local high temperatures. Some raw materials in the local high-temperature area are easily oxidized and lost, and chemical reactions easily occur to generate impurities. These impurities will cause impurity phases to be generated during the subsequent sintering process, affecting the product purity. In addition, the nano-sized particle diameter is too small, and it is not easy to mix the two raw materials evenly during grinding, which will lead to insufficient reaction between the raw materials during subsequent sintering, affecting the consistency of the crystal structure of the product and also causing the generation of impurity phases. Moreover, the nano-sized particle diameter is small. If it needs to be mixed very evenly, the energy consumption required is also high, which is not conducive to achieving the purpose of energy conservation in industrial production.
[0047] The present application uses micron-sized raw materials for mixing, which has the following advantages: the particle sizes of the two micron-sized raw materials are moderate, and the interfacial effect between the tiny particles allows for uniform mixing with lower energy consumption. It is not easy to produce agglomeration between particles during mixing and subsequent crushing, thus avoiding the local high temperature phenomenon caused by particle agglomeration. After the two micron-sized raw materials are evenly mixed and then crushed into nano-sized particles, the mixed raw materials can be crushed into a mixture with a uniform particle size, and a more uniform crystal structure can be obtained in the subsequent sintering process, which is beneficial to increase the reaction activity of the product, avoid the generation of impurity phases caused by the uneven particle sizes of the two raw materials during sintering, and help improve the crystallinity of the sintered product.
[0048] In the above method, after the slurry is dried, the liquid phase in the slurry evaporates, leaving a solid phase. The solvent used to prepare the slurry is water. Because the two different types of mixed particles in the slurry have a uniform particle size, the interaction between the solid phase and the liquid phase is relatively uniform, and the liquid phase can evaporate uniformly, leaving a fluffy solid phase, i.e., dry powder. There are uniform gaps between the nanoparticles in the dry powder, rather than a compact structure, so that the dry powder presents a loose structure as a whole, is not easy to agglomerate, and can avoid agglomeration during the sintering process, thereby avoiding the generation of local high-temperature areas, the occurrence of adverse chemical reactions, and the generation of impurity phases during the sintering process to a certain extent.
[0049] Because fluffy dry powder is formed in the previous step, there are uniform gaps between the solid nanoparticles in the dry powder, and there is enough air in the gaps, so that sintering can be carried out in a sufficient oxygen-containing atmosphere, and it can be uniformly sintered into a stable single phase to obtain a relatively pure lanthanum titanium oxide. In addition, when the lanthanum titanium oxide is used as a precursor to prepare a lithium lanthanum titanium oxide with a perovskite structure, because the purity of the lanthanum titanium oxide is high, the reaction activity is increased, and the lithium source can fully contact and react with the surrounding lanthanum titanium oxide, and there will be no large loss of lithium source during the reaction.
[0050] In addition, nanoscale raw materials are expensive. If nanoscale raw materials are directly selected, the cost burden will be greatly increased. However, the preparation method not only reduces the synthesis temperature but also improves the purity of the product.
[0051] In a specific example, grinding can be a sand milling process, and specifically, the mixed material can be placed in a sand mill for wet crushing, and the material can be ground into a slurry with a nanometer particle size. Those skilled in the art can understand that any existing grinding process that can process the material into a nanometer slurry can be used, for example, a ball milling process that can achieve the above-mentioned processing function can also be used. Drying treatment can select appropriate drying equipment according to the material, for example, the slurry can be spray dried, and the powdery material can be dried. In another embodiment, during mixing, a sintering aid is also added to the raw material to inhibit grain growth, which is conducive to promoting sintering densification. The sintering aid is an oxide. The sintering aid can be selected from any one of aluminum oxide, calcium oxide, and magnesium oxide, and aluminum oxide is most preferably used.
[0052] The slurry is sintered to obtain a lanthanum titanium oxide compound. The lanthanum titanium oxide compound is used to prepare a perovskite-type solid electrolyte. In some embodiments, the sintering may adopt the following process parameters: a sintering temperature of 900°C-1200°C; and / or a sintering time of 10h-48h. In a specific example, the sintering temperature may be any of 900°C, 950°C, 1000°C, 1150°C or 1200°C, or any temperature in the range of 900°C-1200°C. The sintering time may be any of 10h, 20h, 30h, 35h, 40h, 45h or 48h, or any other time in the range of 10h-48h. Controlling within the above-mentioned sintering process parameter range is conducive to the formation of a single-phase lanthanum titanium oxide compound product, which is conducive to improving the crystallinity of the product lanthanum titanium oxide compound, thereby helping to improve the crystallinity of the solid electrolyte.
[0053] In other embodiments of the present application, the lanthanum source compound can be selected from but not limited to any one of lanthanum oxide, lanthanum nitrate, and lanthanum hydroxide, and is most preferably lanthanum oxide. The titanium source compound can be selected from but not limited to one of titanium dioxide, lithium titanate, and barium titanate compounds, and is most preferably titanium dioxide. In other embodiments, the molar ratio of the lanthanum source compound to the titanium source compound is (1-5):(2-4).
[0054] In other embodiments of the present application, the preparation method of the lanthanum titanium oxide compound is: the mixing is wet mixing, and the mass percentage concentration of the solid in the mixture is 12%-13%; and / or the drying is atomization drying. In the above method, wet mixing is performed to prepare the raw materials into a slurry to improve the dispersibility of nano-scale solid particles, thereby facilitating the full mixing of the lanthanum source compound and the titanium source compound, and facilitating the avoidance of the formation of impurity phases in the product.
[0055] In other embodiments of the present application, a lithium battery is provided, which is composed of a solid electrolyte and an electrode, wherein the solid electrolyte is prepared by the preparation method of the solid electrolyte provided in the above embodiment. The solid electrolyte is the core component of the lithium battery and is a key factor affecting the performance of the lithium battery. This embodiment improves the crystallinity of the product lithium lanthanum titanium oxide compound by improving the solid electrolyte preparation process, thereby improving the electrochemical properties of the lithium lanthanum titanium oxide compound, and then improving the conductivity of the solid electrolyte, while reducing energy consumption and reducing costs, thereby improving the conductive properties of the lithium battery and reducing the preparation cost of the lithium battery.
[0056] The technical effects of the present application are further illustrated below in conjunction with specific embodiments.
[0057] Example 1
[0058] This embodiment provides a method for preparing a lanthanum titanium oxide compound, which comprises the following steps:
[0059] Take 16.214g of lanthanum oxide (LaO) and 16.14g of titanium dioxide as raw materials. Add 0.4g of aluminum oxide as a sintering aid to the raw materials; oxygen element is provided by lanthanum oxide and titanium dioxide. The molar ratio of lanthanum oxide to titanium dioxide is 1:4.
[0060] Step 1: Mix lanthanum oxide, titanium dioxide and aluminum oxide through a mixing device to obtain a mixture without pretreatment.
[0061] Step 2: The above mixture is prepared into an aqueous slurry with a solid content of 12%, and poured into a sand mill for sand grinding; the sand grinding process adopts the following process parameters: the diameter of the zirconium beads is 0.2 mm, the rotation speed is 1200 rpm; and the sand grinding time is 3 hours.
[0062] Step 3: spray-dry the ground slurry to obtain fluffy dry powder.
[0063] Step 4: Place the fluffy dry powder into a muffle furnace for sintering at a temperature of 1000° C. and a sintering time of 10 h; after the muffle furnace is cooled, a lanthanum titanium oxide compound is obtained; the lanthanum titanium oxide compound is in the form of a white powder with a particle size of 5 μm.
[0064] The lanthanum titanium oxide compound prepared in this example was subjected to X-ray powder diffraction detection, and the detection results are shown in Figure 1 .from Figure 1 It can be seen that there are main characteristic diffraction peaks at 2θ angles of 32°, 40° and 46°. There are minor peaks at 27°, 30°, 58°, 68° and 77°.
[0065] Example 2
[0066] This embodiment provides a method for preparing a lanthanum titanium oxide compound, which comprises the following steps:
[0067] 16.214 g of lanthanum nitrate (La(NO)) and 5.992 g of titanium dioxide (TiO) were used as raw materials. The oxygen element was provided by titanium dioxide. The molar ratio of lanthanum nitrate and titanium dioxide was 2:3.
[0068] Step 1: Mix the lanthanum nitrate and titanium dioxide mentioned above through a mixing device to obtain a mixture without pretreatment.
[0069] Step 2: The above mixture is prepared into an aqueous slurry with a solid content of 11%, and poured into a sand mill for sand grinding; the sand grinding process adopts the following process parameters: the diameter of the zirconium beads is 0.2 mm, the rotation speed is 1200 rpm; and the sand grinding time is 1 hour.
[0070] Step 3: spray-dry the ground slurry to obtain fluffy dry powder.
[0071] Step 4: Place the fluffy dry powder into a muffle furnace for sintering at a temperature of 900° C. and a sintering time of 15 h; after the muffle furnace is cooled, lanthanum titanium oxide is obtained; the lanthanum titanium oxide is in the form of white powder with a particle size of 7 μm.
[0072] The lanthanum titanium oxide compound prepared in this example was subjected to X-ray powder diffraction detection, and the detection results are shown in Figure 1 .
[0073] Example 3
[0074] This embodiment provides a method for preparing a lanthanum titanium oxide compound, which comprises the following steps:
[0075] 16.214 g of lanthanum oxide (LaO) and 2.56 g of titanium dioxide (TiO) were used as raw materials. The oxygen element was provided by titanium dioxide. The molar ratio of lanthanum oxide to titanium dioxide was 3:2.
[0076] Step 1: Mix the above lanthanum oxide and titanium dioxide through a mixing device to obtain a mixture without pretreatment.
[0077] Step 2: The above mixture is prepared into an aqueous slurry with a solid content of 11%, and poured into a sand mill for sand grinding; the sand grinding process adopts the following process parameters: the diameter of the zirconium beads is 0.8 mm, the rotation speed is 1200 rpm; and the sand grinding time is 2 h.
[0078] Step 3: spray-dry the ground slurry to obtain fluffy dry powder.
[0079] Step 4: Place the fluffy dry powder into a muffle furnace for sintering at a temperature of 1200° C. and a sintering time of 20 hours; after the muffle furnace is cooled down, a lanthanum titanium oxide compound is obtained; the lanthanum titanium oxide compound is in the form of a white powder with a particle size of 5 μm.
[0080] The lanthanum titanium oxide compound prepared in this example was subjected to X-ray powder diffraction detection, and the detection results are shown in Figure 1 .
[0081] Example 4
[0082] This embodiment provides a method for preparing a solid electrolyte, which comprises the following steps:
[0083] Step 1: Weigh the lanthanum titanium oxide compound according to the molar ratio of lithium, lanthanum and titanium of the lithium lanthanum titanium oxide compound being 7:11:20, and weigh micron-sized lithium carbonate according to the ratio of 5% excess lithium carbonate.
[0084] Step 2: Mix the weighed materials and then sinter them at a sintering temperature of 900° C. and a sintering time of 10 h to obtain the target product, lithium lanthanum titanium oxide, i.e., a solid electrolyte.
[0085] The lithium lanthanum titanium oxide compound prepared in this example was subjected to X-ray powder diffraction detection, and the detection results are shown in Figure 2 .Will Figure 2 The diffraction pattern of Figure 3 Compared with the XRD standard card JCPDS NO.87-0935 shown in the figure, it can be seen Figure 2 The crystal form of the lithium lanthanum titanium oxide compound characterized is consistent with the standard card JCPDS NO.87-0935. Figure 3 Compared with the standard peak shown, it can be observed Figure 2 There is no impurity peak in the product, indicating that there is no impurity in the product lithium lanthanum titanium oxide. Figure 2 It can be seen that the diffraction peak is sharp. According to the area ratio of the sharp peak to the broadened diffuse peak, it can be judged that the lithium lanthanum titanium oxide compound obtained in this example has a high crystallinity.
[0086] The conductivity of the lithium lanthanum titanium oxide compound prepared in this embodiment was tested, and the conductivity of the lithium lanthanum titanium oxide compound was 2.13×10 -3 S / cm.
[0087] In summary, the lithium lanthanum titanium oxide compound prepared in this embodiment has high crystallinity and high purity, which is beneficial to improving the electrochemical properties of the lithium lanthanum titanium oxide compound and further improving the conductivity of the solid electrolyte.
[0088] Example 5
[0089] This embodiment provides a method for preparing a solid electrolyte, which comprises the following steps:
[0090] Step 1: Weigh the lanthanum titanium oxide compound according to the molar ratio of lithium, lanthanum and titanium of the lithium lanthanum titanium oxide compound being 7:11:20, and weigh micron-sized lithium carbonate according to the ratio of 10% excess lithium carbonate.
[0091] Step 2: Mix the weighed materials and then sinter them at a sintering temperature of 1000° C. and a sintering time of 10 h to obtain the target product, lithium lanthanum titanium oxide, i.e., a solid electrolyte.
[0092] The lithium lanthanum titanium oxide compound prepared in this example was subjected to X-ray powder diffraction detection, and the detection results are shown in Figure 2 .
[0093] The conductivity of the lithium lanthanum titanium oxide compound prepared in this embodiment was tested, and the conductivity of the lithium lanthanum titanium oxide compound was 1.78×10 -3 S / cm.
[0094] Example 6
[0095] This embodiment provides a method for preparing a solid electrolyte, which comprises the following steps:
[0096] Step 1: Weigh the lanthanum titanium oxide compound according to the molar ratio of lithium, lanthanum and titanium of the lithium lanthanum titanium oxide compound being 7:11:20, and weigh micron-sized lithium carbonate according to the ratio of 7.5% excess lithium carbonate.
[0097] Step 2: Mix the weighed materials and then sinter them at a temperature of 950° C. and a sintering time of 10 h to obtain the target product, lithium lanthanum titanium oxide, i.e., a solid electrolyte.
[0098] The lithium lanthanum titanium oxide compound prepared in this example was subjected to X-ray powder diffraction detection, and the detection results are shown in Figure 2 .
[0099] The conductivity of the lithium lanthanum titanium oxide compound prepared in this embodiment was tested, and the conductivity of the lithium lanthanum titanium oxide compound was 1.211×10 -3 S / cm.
[0100] Of course, the above embodiments cannot be understood as limiting the present application.
[0101] The above is a detailed introduction to the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for general technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a solid electrolyte, characterized in that: It includes: Mixing a lanthanum titanium oxide compound with a lithium source to obtain a mixed material; Sintering the mixed material to obtain a lithium lanthanum titanium oxide compound having a perovskite structure, namely the solid electrolyte, wherein the sintering temperature is 920°C - 1000°C; the sintering time is 8h - 20h; Wherein, the chemical formula of the lanthanum titanium oxide compound is La 2 / 3-x TiO3, of which 0 <x<0.16; The lithium source includes LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, Li2CO3; The particle size of the lanthanum titanium oxide compound is 5μm - 15μm; The particle size of the lithium source is 5μm - 15μm.
2. The method for preparing the solid electrolyte according to claim 1, wherein The total molar ratio of the lanthanum titanium oxide compound to the lithium lanthanum titanium oxide compound is (5 - 3x):(6x + 5), where 0 < x < 0.16; and, The addition amount of the lithium source is 1.05 to 1.10 times the molar amount of lithium in the lithium lanthanum titanium oxide compound.
3. The method for preparing a solid electrolyte according to claim 1, characterized in that: The X-ray diffraction pattern of the lanthanum titanium oxide compound contains characteristic diffraction peaks at 2θ angles of 32 ± 1 degree, 40 ± 1 degree, and 46 ± 1 degree.
4. The method for preparing the lanthanum titanium oxide compound in the method for preparing the solid electrolyte according to claim 1 includes: Mixing a lanthanum source compound with a micron-sized particle size and a titanium source compound with a micron-sized particle size to obtain a mixture; Performing wet grinding on the mixture to obtain a slurry containing mixed particles with a nano-sized particle size; Drying the slurry to obtain a dry powder; Sintering the dry powder to obtain a lanthanum titanium oxide compound.
5. The method for preparing a solid electrolyte according to claim 4, characterized in that: The molar ratio of the lanthanum source compound to the titanium source compound is: (1 - 5):(2 - 4).
6. The method for preparing a solid electrolyte according to claim 4, characterized in that: In the method for preparing the lanthanum titanium oxide compound, the sintering temperature is 900°C - 1200°C; and / or, The sintering time is 10h - 48h; and / or, When performing the mixing, a sintering aid is further added, The sintering aid is an oxide.
7. The method for preparing a solid electrolyte according to claim 4, characterized in that: In the method for preparing the lanthanum titanium oxide compound, the mixing is wet mixing, and the mass percentage concentration of the solid matter in the mixture is 12% - 13%; and / or, The drying is spray drying.
8. A lithium battery, characterized in that: It includes the solid electrolyte prepared by the preparation method according to any one of claims 1 - 7.
Citation Information
Patent Citations
Single crystal film with two-dimensional electron gas and preparation method thereof
CN114197048A
Organic electroluminescent device and display using same
CN1817063A
Composition for forming solid electrolyte layer, method for forming solid electrolyte layer, solid electrolyte layer, and lithium ion secondary battery
US20130122376A1